Analysis Of Factors Related To Subjective Well-Being In Diabetes Mellitus Patients In Banjarbaru Region - Yulyanti, Yulyanti; Wahana, Hijratun; Yunita, Yunita; Negara, Candra Kusuma (Jurnal EduHealth, 2024)
Diabetes Mellitus is a chronic disease with increased blood glucose levels because the body cannot produce enough insulin hormone. Changes in diabetes mellitus patients who view their disease condition negatively need to be reviewed from a psychological perspective. Factors related to subjective well-being values in people with diabetes mellitus need to be identified and improved as an initial step so that later they are able to exercise positive control over themselves. This study used a cross-sectional design using a random sampling method with inclusion and exclusion criteria. The total respondents were 102 people with Diabetes mellitus. Furthermore, the data were analyzed using the Spearman Rank test with a significance level <0.05. The results of the demographic data obtained 81 female respondents, aged 46-55 years and married. There is a significant relationship between subjective well-being and personality (ρ = 0.008), and demographic factors including family support (ρ = 0.011), and religiosity (ρ = 0.029). Meanwhile, contextual and situational factors (ρ=0.636), and demographic factors including gender (ρ=0.613), and employment status (ρ=0.414) did not have a significant relationship with subjective well-being in diabetes mellitus patients in the Banjarbaru area.